Highly selective electrocatalytic reduction of CO2 to HCOOH over an in situ derived hydrocerussite thin film on a Pb substrate. (March 2022) - Wang, Da; Dong, Shiwen; Wen, Lingsha; Yu, Weiting; He, Zhiqiao; Guo, Qingqing; Lu, Xiaohui; Wang, Lizhang; Song, Shuang; Ma, Jun
Abstract: A metal oxide electrode has been developed for the electrochemical CO2 reduction reaction (eCO2 RR). It exhibits superior activity and product selectivity towards eCO2 RR by circumventing the previously encountered problem of self-reduction with high-valence metals. Specifically, a hydrocerussite [Pb3 (CO3 )2 (OH)2 ] thin film has been synthesized in situ on a Pb substrate (denoted as ER-HC) by an electroreduction method using a lead-based metal–organic framework (Pb-MOF) as a precursor. The ER-HC electrode exhibits a high selectivity of 96.8% towards HCOOH production with a partial current density of 1.9 mA cm −2 at −0.88 V vs. the reversible hydrogen electrode (RHE). A higher HCOOH partial current density of 7.3 mA cm −2 has been achieved at −0.98 V vs. RHE. Physicochemical and electrochemical characterization results demonstrate that the defective hydrocerussite surface exhibits appropriate adsorption free energy of formate (HCOO − ) and a lower reaction free energy for HCOOH production from CO2, which greatly boosts the eCO2 RR activity and HCOOH production selectivity. The structure and eCO2 RR performance of the hydrocerussite thin film remain stable in 0.1 M KHCO3 as electrolyte, ensuring its durability. Overall, this work not only provides a metal oxide electrode (metal hydroxide, to be more precise) with excellent eCO2 RR performance, but also expands the in situ electrochemical derivatization strategy for the fabrication of metal oxide electrodes. Graphical abstract: Image 1 Highlights: Hydrocerussite thin film (ER-HC) was prepared via electrochemical derived Pb-MOF. The Pb ions in Pb-MOF and KHCO3 in electrolyte were converted to stable ER-HC. ER-HC exhibited high electrochemical CO2 reduction activity and durability. The FE of HCOOH could reach 96.8% at −0.88 V vs. RHE with ER-HC. Surface defects on ER-HC were active sites.